2014
DOI: 10.1111/jdv.12769
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic difficult lesions: an objective evaluation of reflectance confocal microscopy impact for accurate diagnosis

Abstract: Background Early detection of melanoma is the main objective to ensure a high survival rate. In some cases melanoma diagnosis still remain difficult and this leads to unnecessary excisions. Objective The aim of this study was to detect the most relevant Reflectance confocal microscopy (RCM) features for the detection of dermoscopic difficult melanomas. Method A total of 322 lesions were selected from database and were evaluated on dermoscopy according to the 7‐point checklist score, in blind from histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 25 publications
1
39
0
2
Order By: Relevance
“…In contrast, only 17.7% (n = 30) of nevi were incorrectly diagnosed as melanoma (false positive). 30 In addition, RCM was also found to be helpful in evaluating small-diameter (ie, incipient melanomas) melanomas. 31 With RCM, the combination of cytologic atypia with cellular pleomorphism and architectural disorder with irregular clods was found to be strong criteria for the identification of incipient melanomas.…”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
“…In contrast, only 17.7% (n = 30) of nevi were incorrectly diagnosed as melanoma (false positive). 30 In addition, RCM was also found to be helpful in evaluating small-diameter (ie, incipient melanomas) melanomas. 31 With RCM, the combination of cytologic atypia with cellular pleomorphism and architectural disorder with irregular clods was found to be strong criteria for the identification of incipient melanomas.…”
Section: Role Of Reflectance Confocal Microscopy In Detecting Melanommentioning
confidence: 99%
“…RCM may be especially helpful in difficult lesions, where clinical and dermoscopic features are not straightforward[14-17]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have consistently suggested that the addition of RCM to dermoscopy decreases the "number needed to treat" 19,20,29 and patient management costs. Two recent studies 2,19 evaluated the use of RCM in combination with digital dermoscopy in a very similar clinical setting to that described here, and found that the combination of these two diagnostic tools could have prevented the excision of 27 of 58 and 35 of 51 nevi, respectively, a proportion very similar to that reported in the present series (46/87).…”
Section: Discussionmentioning
confidence: 99%